A circle of uncommon witches - Crutcher, Paige (St. Martin's Griffin, 2025)
"Doreen MacKinnon is doomed to die of a broken heart - if she can't break the centuries old curse placed on her family. Three hundred years ago, Ambrose MacDonald, a powerful male witch, fell in love with a MacKinnon. And when the MacKinnon witches forbade him from seeing his love, by secretly hiding her away, he retaliated by cursing the family and its future generations to never find love. But it wasn't without a cost. Now, Ambrose is imprisoned by those same witches, trapped in a tempest and doomed to outlive everyone he has ever loved. But Doreen isn't like the other MacKinnon witches. As the 13th generation of the MacKinnon line, Doreen is one of the most powerful witches in centuries... and one of the loneliest. So when she discovers where Ambrose has been trapped, she releases him to help her break the curse, once and for all. Ambrose agrees to help, but with his own motive: vengeance. He plans to use her as bait to enact his revenge on her family. Together, they enter a series of trials, which take them to a castle in Scotland, off a cliff, and into a world beyond their wildest dreams. As they work together, sparks start to fly, but soon Doreen must choose how far she is willing to go to break the curse, and what she's willing to sacrifice."--